Functional Outcome of Displaced Diaphyseal Both Bone Forearm Fracture in Children Treated with Elastic Stable Intramedullary Nails - DC, Gopal Sagar (Journal of Nepalgunj Medical College, 2018)
Introduction: Pediatric forearm fractures are most commonly managed by closed reduction and above elbow cast. Failure to achieve anatomical initial reduction, tight cast and re-displacement within cast leading to malunion are common complication. Elastic stableintramedullary nailing for such fracture gives more predictable result with minimal morbidity. We studied on functional outcome of such fracture treated operatively with elastic stable intramedullary nail in our center. Methods: This prospective descriptive study was done in Nepalgunj Medical College Hospital, Nepalgunj between January 2015 to May 2017.It included 47 pediatric patients (5-15 years) with displaced both bone forearm diaphyseal fracture. All fractures were fixed with elastic stable intramedullary nails of appropriate size under general anesthesia. Cases were followed up at 1, 2, 4, 6, 8, 10, 12 weeks and at 6 month functional outcome was evaluated using price criteria. Data were entered in structured proforma and statistical analysis was carried out using SPSS 20.0. Results: Out of 47 cases included in our study, mean age of patient was 9.7 years (range 5-15 years). 31(65.9%) cases were male and16 (34.1%) were female. 42(89.4%) cases had closed fracture and 5(10.6%) had grade I open factor. 40(85.1%) cases were operated by closed technique. Average hospital stay was 2.7±1.8 day (range 2-5days). Radiological union was achieved on 6.5±2.7 weeks (range 6-11weeks).Functional outcome in final follow up at 6 month was excellent in 36(76.6%), good in 9(19.1%) and fair in 2(4.3%) cases. Superficial surgical site infection was seen in 3 cases (6.3%) and exposure of nail tip was seen in 2 cases (4.2%). Conclusion: Elastics table intramedullary nail for displaced pediatric both bone forearm diaphyseal fracture is biological osteosynthesis, simple and reproducible treatment with excellent functional outcome with minimal morbidity.